An Experimental Group A Streptococcus Vaccine That Reduces Pharyngitis and Tonsillitis in a Nonhuman Primate Model - Rivera-Hernandez, Tania (mBio, 2019)
Group A Streptococcus (GAS) infections account for an estimated 500,000 deaths every year. This bacterial pathogen is responsible for a variety of mild and life-threatening infections and the triggering of chronic autoimmune sequelae. Pharyngitis caused by group A Streptococcus (GAS), but not asymptomatic GAS carriage, is a prerequisite for acute rheumatic fever (ARF). Repeated bouts of ARF may trigger rheumatic heart disease (RHD), a major cause of heart failure and stroke accounting for 275,000 deaths annually. A vaccine that prevents pharyngitis would markedly reduce morbidity and mortality from ARF and RHD. Nonhuman primates (NHPs) have been utilized to model GAS diseases, and experimentally infected rhesus macaques develop pharyngitis. Here we use an NHP model of GAS pharyngitis to evaluate the efficacy of an experimental vaccine, Combo5 (arginine deiminase [ADI], C5a peptidase [SCPA], streptolysin O [SLO], interleukin-8 [IL-8] protease [SpyCEP], and trigger factor [TF]), specifically designed to exclude GAS components potentially linked to autoimmune complications. Antibody responses against all Combo5 antigens were detected in NHP serum, and immunized NHPs showed a reduction in pharyngitis and tonsillitis compared to controls. Our work establishes the NHP model as a gold standard for the assessment of GAS vaccines.